DYŻUR MEDYCZNY A CZAS PRACY W ŚWIETLE ORZECZEŃ TRYBUNAŁU KONSTYTUCYJNEGO, SĄDU NAJWYŻSZEGO I EUROPEJSKIEGO TRYBUNAŁU SPRAWIEDLIWOŚCI - Porażyńska, Małgorzata (Wydział Prawa i Administracji UAM, 2004)
The article is devoted to the issue of medical duty hours in the context of working hours against the background of current legal regulations and verdicts of the Polish Supreme Court, Polish Constitutional Tribunal and the European Court of Justice. The large collection of verdicts of the Constitutional Tribunal and the Supreme Court have been the result of inappropriate legal regulations that, as incompliant with the Constitution, have been giving rise to claims for compensation for duty hours as overtime work. The author makes an attempt to determine the real meaning of the legal norm included in art. 32j section 2 of the Health Care Institutions Act dated 30 Aug 1991 and following an analysis of the verdicts of the European Court of Justice and the provisions of Directive 93/104/EC dated 23 Nov 1993 on some aspects of work time organisation, she indicates the need to immediately amend the aforesaid Polish act in this respect.
MEDICAL DUTY HOURS VS. WORKING HOURS IN THE LIGHT OF VERDICTS OF POLISH CONSTITUTIONAL TRIBUNAL, SUPREME COURT AND EUROPEAN COURT OF JUSTICE